A rare recurrent case of lateral nasal wall schwannoma: mimicking sinonasal carcinoma - Kumari, Diksha; Hoda, Zaufashan; Singh, Anju; Kumar, Amit; Raj, Rohit; Sinha, Richi; Singh, Rakesh Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Schwannomas are rare, benign, and slow-growing tumors that originate from the Schwann cells of peripheral nerves. They exhibit no sex predilection and are often characterized by a variable and delayed clinical presentation. The definitive diagnosis is established through histopathological examination. In this report, we present a rare case of a schwannoma arising from the lateral wall of the nasal cavity in a 45-year-old male patient. The tumor was successfully excised via endoscopic nasal surgery, and there was no recurrence observed at six-month follow-up.